Characterization of Palm Frond Biochar and Coconut Shell Biochar on Peaty Soil Physical - Ike Ramadhona; Hapsoh Hapsoh; Besri Nasrul Nasrul (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2023)
Using plantation crop residues in the form of oil palm fronds and coconut shells has the potential as a soil ameliorant material such as Biochar. Using Biochar as an ameliorant can improve soil fertility, one of which is peaty soil with a very acidic pH. The research aims to analyze the basic characterization of Biochar palm fronds and coconut shells on the physical properties of peaty soil. Palm fronds and coconut shells were pyrolyzed using a simple combustion device in the form of a pyrolysis drum. Combustion with pyrolysis drums is carried out in a closed manner in the absence of oxygen for 2-5 hours. Parameters observed were lignocellulose of palm fronds and coconut shells, spectrographs, chemical properties of Biochar of palm fronds and coconut shells, and physical properties of peaty soil after applying Biochar of palm fronds and coconut shells. The pH, total C, total N, C/N, total P, available P, total K, total Na, and the volume and pore size of the coconut shell biochar showed higher results than the palm frond biochar. However, the results of the analysis of total Mg, total Ca, CEC and ash content and surface area on palm frond biochar showed higher results than coconut shell biochar. The moisture content and BD values of peaty soil in applying coconut shell Biochar showed the best results compared to palm frond biochar.